2016
DOI: 10.1007/s11356-015-5931-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dioxin exposure upon levels of prostate-specific antigen and steroid hormones in Vietnamese men

Abstract: Most studies on the relationship between Agent Orange and prostate cancer have focused on US veterans of the Vietnam War.There have been few studies focusing on the relationship between levels of prostate-specific antigen (PSA) and dioxins or steroid hormones in Vietnamese men. In 2009-2011, we collected blood samples from 97 men who had resided in a "dioxin hotspot" and 85 men from a non-sprayed region in Vietnam. Then, levels of PSA, dioxins, and steroid hormones were analyzed. Levels of most dioxins, furans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…As before, there was also no effect related to cortisol in the longitudinal analyses. The results of this study confirmed previous studies that also found a positive association between PCB exposure and DHEAS concentration, but none between PCB exposure and cortisol concentration [2,15,16].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As before, there was also no effect related to cortisol in the longitudinal analyses. The results of this study confirmed previous studies that also found a positive association between PCB exposure and DHEAS concentration, but none between PCB exposure and cortisol concentration [2,15,16].…”
Section: Discussionsupporting
confidence: 91%
“…However, a subsequent study found a positive association between PCB exposure and the DHEAS concentration in male employees [ 2 ]. Sun et al also report a significant increase in DHEA concentration with increased PCB body burden in men [ 16 ]. High DHEAS inhibits genetically programmed cell death [ 17 ], and this enhances the risk for cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A study of men living in areas of Vietnam with high dioxin contamination found no difference in prostate-specific antigen concentrations between control and high serum dioxin groups [47]. Also, the Vietnamese men with high serum dioxin showed increased testosterone and estradiol levels, but decreased dehydroepiandrosterone levels, and no change in other steroid hormones [48]. Exposure to dioxin-contaminated food was associated with a decrease in total and free testosterone [49], although (as noted above) several studies have not found TCDD exposure to alter semen quality or sperm count (reviewed in [50]).…”
Section: Discussionmentioning
confidence: 99%
“…Among the output studies, two studies examined PCBs in food and did not measure their levels in serum and plasma (Ali et al, 2016; Pavuk et al, 2004). In three studies, prostate antigen levels and carcinogenic biomarkers were measured and no cancer incidence was reported (De Coster et al, 2008; Hardell et al, 2006; Sun et al, 2016). One study examined the association between PCBs and mortality from prostate cancer (Fernandez-Navarro et al, 2017).…”
Section: Resultsmentioning
confidence: 99%